Dirt(y) media: Dirt in ecological media art practices. (February 2023) - Kelly, Caleb
While we may imagine that the unblemished surfaces of our shiny devices are free from the grime of the everyday – flawless and pure – we do not have to dig far below the surface to find that these technologies are anything but untainted and dirt-free. This realisation is at the heart of a shift in international media art towards materials based media. While there have been numerous books and papers describing a materials based media within the notion of 'media ecologies', there is more to be learnt from media art, an area that both critiques media and information, and which develops practices that engage in issues around the materiality of media technologies. This article will specifically address dirt through media ecologies by investigating how media artists have made their work literally dirty. The first section of the article critically addresses the notion of media as being material, as opposed to the imagined as pristine, pure and immaterial, and being so, is able to become dirty. The second section looks to a pre-history of dirt(y) media found in the work of artists Milan Knížák and Christian Marclay. The remainder of the article discusses a shift in the approach to contemporary media art that turns away from the digital studio towards a resolutely analogue and physical practice.